Pengaruh Harga terhadap Keputusan Pembelian dengan Menggunakan Niat Beli Produk Skincare Skintific sebagai Variabel Intervening - Layinatul Masruroh; Muhammad Roni Indarto (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2024)
This research aims to determine the effect of price on purchasing decisions with purchase intention as an intervening variable in Skintific skincare products. The population in this study were consumers who had purchased and used Skintific skincare products at least twice. . The sample in this study was 103 samples. The data collection technique uses a questionnaire with Likert scale measurements and uses a purposive sampling technique. This research uses macro path analysis with the IBM SPSS Statistics 26 tool. The results of this research show: (1) Price influences purchasing decisions (2) Price influences purchasing interest, (3) Purchase interest influences purchasing decisions, (4) Price influence purchasing decisions through purchase interest